1975
DOI: 10.1177/000348947508400402
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Facial Paralysis, Pregnancy, and the Menstrual Cycle

Abstract: The records of 42 women with Bell's palsy during pregnancy, and of 91 nonpregnant women, whose dats of onset of Bell's palsy and of the preceding menstrual cycle were precisely known, were studied for factors that might show relation between pregnancy or the menstrual cycle and Bell's palsy. Of the 42 cases in pregnancy, 31 occurred in the third trimester, five in the first two weeks postpartum, and six in the first two trimesters combined. Our calculated frequency of Bell's palsy in pregnant women is 45.1/100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
13

Year Published

1976
1976
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(68 citation statements)
references
References 33 publications
2
48
0
13
Order By: Relevance
“…For instance, Adour et al [12 ]found that among individuals 10–19 years of age, BP was twice as common in females and postulated that this observation may have pertained to menarche. In addition, pregnancy appears to be a risk factor for BP potentially due to physical or hormonal changes [21]. In our study, the incidence rate of BP was higher among females than males across all age strata, even among young children, and only 3 cases were pregnant at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 58%
“…For instance, Adour et al [12 ]found that among individuals 10–19 years of age, BP was twice as common in females and postulated that this observation may have pertained to menarche. In addition, pregnancy appears to be a risk factor for BP potentially due to physical or hormonal changes [21]. In our study, the incidence rate of BP was higher among females than males across all age strata, even among young children, and only 3 cases were pregnant at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 58%
“…Contrary to diabetes there is less evidence in the literature for hypertension to cause or predispose to Bell’s palsy in the general population [5,6,7,12,13,14,15,28,29,30]. There has been more attention on hypertension in Bell’s palsy among children and pregnant women [31,32,33,34,35,36,37]. The incidence of Bell’s palsy is significantly higher during the last trimester of pregnancy and the puerperium.…”
Section: Discussionmentioning
confidence: 99%
“…Kortikosteroiden ist im HNO-ärztlichen Bereich anerkannt Auch die Prognose der Fazialisparese in der Schwangerschaft wird uneinheitlich beurteilt [6,13,20]. Hierbei scheint die inkomplette periphere Fazialisparese eine günstigere Prognose zu haben als die vollständige Gesichtsnervenlähmung, bei der Defektheilungen in bis zu 50% der Fälle beschrieben sind [20,24].…”
Section: » Die Therapie Mitunclassified
“…Für die Normalbevölkerung wird eine Inzidenz von 20-30/100.000 mit einem Altersgipfel zwischen 20 und 35 Jahren und einem bilateralen Auftreten in bis zu 2% der Fälle angenommen [22]. In der Schwangerschaft und Stillzeit ging man bisher von einer signifikant höheren Inzidenz aus [2,13].…”
Section: Diskussionunclassified
See 1 more Smart Citation